PENGARUH PUPUK KASCING DAN SP-36 TERHADAP BEBERAPA SIFAT KIMIA TANAH DAN HASIL TANAMAN BUNCIS PADA FLUVENTIC EUTRUDEPTS ASAL JATINANGOR KABUPATEN SUMEDANG - Emma Trinurani Sofyan (UIR Press, 2014)
The experiment was conducted in order to find out the effects of earthworm casting and SP-36 fertilizer on some soil chemical properties and Kidney bean yield (Phaseolus vulgaris L.) on Fluventics Eutrudepts. The experiment was carried out from March 2013 to November 2013 in green house of Faculty of Agriculture, Padjadjaran University Jatinangor, Sumedang West Java at ± 745 m above sea level. The experiment was a Randomized Block Design of Factorial Patern which consisted of two unit experiments and two factors and three replications. The first factor was earthworm casting in fourth level (0 t ha-1, 7.5 t ha-1, 15 t ha-1 and 22.5 t ha-1). The second factor was SP-36 in fourth level (0 kg ha-1, 100 kg ha-1, 200 kg ha-1 and 300 kg ha-1). The results of experiment showed that there was an interaction effect between earthworm casting with SP-36 fertilizer on C-organic, Available Phosphor, and Kidney bean yield. The application of earthworm casting and SP-36 fertilizers made the single effect on soil acidity. Earthworm casting dosage of 29.94 t ha-1 and SP-36 kg ha-1 gave the highest result on Fluventic Eutrudepts, that is 61.27 g plant-1 and equivalent to 15.32 t ha-1.